Simbolno-številčno analiziranje nihanj sistemov z velikim številom stopenj prostosti - Kulvietiene, Regina (Strojniški vestnik, 2006)
Computer algebra techniques were applied to analyze the vibrations of systems with many degrees of freedom. For this purpose, two solution methods were compared from the computer algebra point of view, and the harmonic balance method was chosen. The system is divided into linear and nonlinear parts. The linear part of the system can be formalized as usual, and symbolic computations were applied to perform a closed-form solution of the nonlinear part. The symbolic-numeric approach chosen, specially dedicated to systems with many degrees of freedom, affords various advantagesČ it leads to a simplification of the theoretical formulation of the models, a considerable reduction in the size of the generated equations, and hence in the resulting computing time, and also enhanced portability of the multibody models to other specific environments.
Keywords: nihanje; prostostne stopnje; algebra